2004
DOI: 10.1159/000078100
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Prodynorphin cDNAs from the Brain of Australian and African Lungfish: Implications for the Evolution of the Prodynorphin Gene

Abstract: In mammals the opioids Met-enkephalin and Leu-enkephalin are derived from a common precursor, proenkephalin, and as a result these neuropeptides are co-localized in enkephalinergic neurons. The mammalian scheme for enkephalinergic networks is not universal for all classes of sarcopterygian vertebrates. In an earlier study, distinct Met- and Leu-enkephalin-positive neurons were detected in the central nervous system (CNS) of the African lungfish, Protopterus annectens. More recently, characterization of proenke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It is unclear if the antisera used for Leu-enkephalin in this study would distinguish leucine from isoleucine-enkephalin as we would predict would be a cleavage product of esPENKL2. A separation of the genes encoding of Met-enkephalin and Leu-enkephalin into two genes has already been observed in several non-mammalian vertebrate species (Dores et al, 2004).…”
Section: Discussionmentioning
confidence: 86%
“…It is unclear if the antisera used for Leu-enkephalin in this study would distinguish leucine from isoleucine-enkephalin as we would predict would be a cleavage product of esPENKL2. A separation of the genes encoding of Met-enkephalin and Leu-enkephalin into two genes has already been observed in several non-mammalian vertebrate species (Dores et al, 2004).…”
Section: Discussionmentioning
confidence: 86%
“…PENK-derived ENKs act as endogenous ligands for δand µ-opioid receptors, which may be involved in emotion regulation activities, such as euphoria, and rewarding behavior [15,16]. Studies have shown that the PENK gene is involved in addiction and rewarding behavior [17,18]. Although the positive neurons of Mek and Lek have been significantly detected in the nervous system of African lungfish [19], Penk has not been extensively characterized in mandarin fish.…”
Section: Introductionmentioning
confidence: 99%
“…Dynorphins are endogenous opioid peptides encoded by a common proenkaphalin-B gene (hereafter referred to as preprodynorphin, PDYN) (Civelli et al, 1985) that is widely expressed in the central and peripheral nervous systems of vertebrates (Cone et al, 1982;Goldsmith et al, 1992;Dores et al, 2004;Shirayama et al, 2004;Alrubaian et al, 2006). As for various peptide hormones, dynorphins are synthesized as large, biologically inert precursor proteins that undergo post-translational modifications to produce biologically active molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Cloning and sequence analysis of the preprodynorphin cDNA revealed that it is a highly conserved gene, although some discrepancies have been described in lower ectotherms. In fish and amphibians, the gene encoding PDYN contains an additional opioid sequence for leucine-enkephalin or isoleucine-enkephalin (Dores et al, 2004;Alrubaian et al, 2006) and for methionine-enkephalin (Danielson et al, 2002), respectively. Although the gene encoding PDYN has not been cloned to date in reptiles, different dynorphins such as -neo-endorphin, dynorphin A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) , dynorphin A (1)(2)(3)(4)(5)(6)(7)(8) and dynorphin B (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) in the lizard Anolis carolinensis and -neo-endorphin and dynorphin B (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) in turtle and alligator have been demonstrated by Goldsmith and colleagues …”
Section: Introductionmentioning
confidence: 99%